2017
DOI: 10.1016/j.jclepro.2017.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different factors in the life cycle assessment of mixed municipal solid waste management systems – A comparison of case studies in Finland and China

Abstract: Influence of different factors in the life cycle assessment of mixed municipal solid waste management systemsa comparison of case studies in Finland and China

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 22 publications
2
18
0
Order By: Relevance
“…In a thorough LCA work comparing different waste management scenarios in Macau, Song et al reported waste transportation as one of the most impacting activities, especially when regarding resources depletion [63], contributing to oil consumption as well as NO x production. This was recently corroborated in studies conducted to assess different possible municipal solid waste management scenarios for the island of Mauritius [64] and also for selected areas in China and Finland [65]. Observing Figure 12 it may be seen that these different boundaries do not interfere significantly in the correlation between both scenarios, meaning that the global performance of the incineration plant is not affected by these modifications.…”
Section: Sensitivity Analysissupporting
confidence: 57%
See 3 more Smart Citations
“…In a thorough LCA work comparing different waste management scenarios in Macau, Song et al reported waste transportation as one of the most impacting activities, especially when regarding resources depletion [63], contributing to oil consumption as well as NO x production. This was recently corroborated in studies conducted to assess different possible municipal solid waste management scenarios for the island of Mauritius [64] and also for selected areas in China and Finland [65]. Observing Figure 12 it may be seen that these different boundaries do not interfere significantly in the correlation between both scenarios, meaning that the global performance of the incineration plant is not affected by these modifications.…”
Section: Sensitivity Analysissupporting
confidence: 57%
“…The electric power generation revealed very prone to the success of the incineration facilities (as in general in EU-27 region) and also in other reported studies [45,46,65], but this is not always true. Depending on the type of resources utilized to compose the grid mix electricity available for the consumer, the avoided impacts generated by the electricity provided from incineration will be different and sometimes not so significant [59].…”
Section: Life Cycle Impact Analysismentioning
confidence: 87%
See 2 more Smart Citations
“…MSW LCA case studies and scenario analysis: Many case studies have been conducted based on different geographical distributed MSWM systems, such as systems based in China [ 23 , 30 ], Sao Paulo, Brazil [ 31 ], Finland and China comparison [ 32 ], Sakarya, [ 33 ], Naples, Italy [ 34 ], Lahore, Pakistan [ 35 ], Bolivia [ 36 ], and France [ 37 ]. Scenario analysis is a commonly used method in the conduction of MSW comparative studies [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ].…”
Section: Introductionmentioning
confidence: 99%